Geometric and Dynamic Patterns of the Golmud Segment in the Southern Marginal Fault of the Qaidam Basin - Luo, Hao; Wang, Ji; Gou, Yasen; Yu, Hongmei; Shu, Peng; Gao, Zhanwu (Frontiers in Earth Science, 2021)
The southern marginal fault of the Qaidam Basin (SMQBF) is a block-bounding border fault that has played a key role in the structural evolution of the Kunlun Fault. However, its geometric and dynamic deformation patterns since the Late Pleistocene have not been well established. Field investigations, combined with high-resolution imagery and shallow seismic profiles, show that the SMQBF is a thrust fault with a sinistral strike-slip component composed of several secondary faults. Its Late Quaternary deformation pattern is characterized by piggyback thrust propagation, and the frontal fault may not be exposed to the surface. Due to the flexural slip of the hanging strata of the secondary fault, sub-parallel faults with widths of thousands of meters have formed on high terraces, and are important when assessing the seismic risk of this area. Based on high-resolution topographic data obtained using an unmanned aerial vehicle and optically stimulated luminescence chronology, the slip rates of several secondary faults were obtained. The vertical and strike-slip rates of the SMQBF were determined to be 0.96±0.33 mm/a and 2.66±0.50 mm/a, respectively, which may be the minimum rates for the fault. Considering that the SMQBF is composed of several secondary faults, these rates may only show the minimum deformation. The evident sinistral strike-slip of the SMQBF indicates though the sinistral slip of the Kunlun Fault system concentrated in its main fault, its branch faults have an important influence on the lateral extrusion of the Qinghai-Tibet Plateau.